2022
DOI: 10.1155/2022/8010395
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical Composition and Biological Evaluation of Typha domingensis Pers. to Ameliorate Health Pathologies: In Vitro and In Silico Approaches

Abstract: Human diseases are becoming more prevalent, necessitating the development of modalities to overcome the challenges of treating various disorders. In the current research, we analyzed the biomedicinal role of Typha domingensis which is an important medicinal plant. The species is traditionally used in the treatment of neurological disorders and skin malignancies. The chloroform (CFTD) and n-butanol fractions of T. domingensis (BFTD) were subjected to chemical profiling through the determination of total polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The reducing antioxidant potential of different fractions and methanolic extract of V. officinalis was evaluated by two methods namely cupric ion reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP) assays in accordance with the modified procedure reported in the literature [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reducing antioxidant potential of different fractions and methanolic extract of V. officinalis was evaluated by two methods namely cupric ion reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP) assays in accordance with the modified procedure reported in the literature [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ABTS activity significantly increased after ultrasonic treatment (P <0.05) and the values were detected as 4.06±0.08 mg Trolox/g dry matter for ethanol extract and 3.90±0.07 mg Trolox/g dry matter for methanol extract. Dilshad et al (2022) conducted a study evaluating phytochemical potential of methanol extract and n-hexane fraction of T. domingensis. They found the ABTS value of methanolic extract as 114.31 mg Trolox/g dry matter, which is higher than this study.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Table 2. Chemical composition (g/kg of dry matter) of typha silages treated with no additive (CON); with formic acid (FA); with urea and molasses (UM); or with formic acid, urea, and molasses (FAUM) of typha biomass before ensiling and of a triticale hay used as a reference 1 . The chemical composition of the typha used in the present study was similar to that reported by de Evan et al [4] for samples of Thypha domingensis collected in Nigeria and by Wingching-Jones and Leal-Rivera [31] for Thypha domingensis collected in Costa Rica.…”
Section: Chemical Composition and Characteristics Of Silagesmentioning
confidence: 99%
“…is made up of between 10 to 15 species of aquatic plants, commonly known by the name of cattail, which refers to its inflorescence. These plants are distributed throughout tropical and subtropical ecosystems, and are found in moist soils, swamps, marshes, or brackish seas throughout the world [1]. Its characteristics, growth pattern, great adaptability to different environmental conditions, and release of compounds that prevent the growth of other plants, give Typha spp.…”
Section: Introductionmentioning
confidence: 99%